Computational Study of the Influence of Structure on Antioxidant Activity and Drug Score of Coumarin Derivatives - Bakti, Andi Budi; Martoprawiro, Muhamad Abdulkadir (Jambura Journal of Chemistry, 2025)
The presence of reactive oxygen species (ROS) in the body must be maintained at low concentrations, excessive ROS and an inability to neutralize them can lead to oxidative stress. Coumarin, a secondary metabolite in plants, is used in pharmacology as an antioxidant agent. This study aims to identify the effects of the type, number, and position of substituents on coumarin derivatives's antioxidant activity and drug score using DFT methods. Computational tools, including ORCA software and OSIRIS Property Explorer, were employed. The results indicate that the number and position of electron-donating substituents, such as OCH3, enhance antioxidant activity, while electron-withdrawing substituents, like CHO, decrease it. Additionally, the presence of conjugated double bonds in the pyrone ring causes electron delocalization, complicating electron transfer. The compound 6,7-dimethoxyhydrocoumarin (hydroscoparone) shows potential as a new antioxidant due to its energy gap similar to commercial antioxidants like ascorbic acid and TBHQ, and a drug score of 0.5 with very low toxicity risk. However, further research is needed to confirm that this compound can be used as an effective antioxidant without side effects.